Nilai-Nilai Pendidikan Islam Dalam Surat Al-A’raf Ayat 26 Berdasarkan Tafsir Ibnu Katsir - Sudin, Mahmudin; Fauzi, Muhammad Ali; Karimah, Ummah; Bahri, Saiful; Hadiyan, Hadiyan (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2023)
This research aims to determine the values of Islamic education contained in Surah Al-A'raf verse 26 based on Ibn Katsir's interpretation. This research is qualitative research, with a library research approach, the research is studied through library research with qualitative data whose sources of information are studied literary sources and the Tafsir Book. Data collection techniques use primary and secondary data. Meanwhile, data analysis uses deductive-inductive methods, comparative methods and content analysis. The research results show that the meaning of Surah Al-A'raf Verse 26 according to Ibnu Katsir in his Tafsir has 3 values of Islamic education, namely, the value of aqidah education (increasing faith and fear of Allah SWT), the value of worship education (praying to Allah SWT and doing good deeds pious), and the value of moral/moral education (wearing Islamic clothing and smiling at others).